Optimization Of Integrated Assessment Team In Aspects Of Prosecution Of Narcotics - Indah Maulani; Rina Arum Prastyanti (Veteran Justice Journal, 2021)
Abstract Research with the formulation of the problem of how the optimization of the integrated assessment team in the aspect of prosecution tindak pidana narcotics which aims to describe the optimization of the integrated assessment team in the aspect of prosecution of narcotics crimes based on qualitative doctrinal approach methods. Therefore, in this study, it is preferable to secondary data collected by literature studies. The data that has been processed for further analysis is qualitatively analyzed. Based on result of research found that narcotics abusers who undergo legal proceedings at the stage of investigation or prosecution can undergo medical rehabilitation and social rehabilitation after going through the assessment process. The assessment process is carried out by an Integrated Assessment Team consisting of a Legal Team and a Team of Doctors. Through the Integrated Assessment Team will be determined whether a suspect or accused drug abuser as a dealer or narcotics addict and through the Medical Team will be tested for the content and severity of narcotics users. If based on the examination of the Integrated Assessment Team is decided to undergo medical rehabilitation, then the suspect or accused drug abuser will be handed over to the rehabilitation institution. Coordination between investigators or public prosecutors and medical rehabilitation institutions can be seen from the beginning of submission, implementation, to the handover to the investigator or public prosecutor. Especially for rehabilitation carried out by outpatient, the authority to present suspects or defendants who are rehabilitated is in the institution that submits (investigators or prosecutors). Keywords: Assessment; prosecution; narcotics crimes.